2016
DOI: 10.1590/1679-395129371
|View full text |Cite
|
Sign up to set email alerts
|

Participação das organizações da sociedade civil na cooperação Sul/Sul: em busca de um modelo de análise nos estudos em administração

Abstract: Resumo Este artigo se propõe a discutir a participação de organizações da sociedade civil brasileiras no âmbito da cooperação para o desenvolvimento. Trata-se de um artigo teórico que procura problematizar os processos de cooperação para o desenvolvimento e construir um quadro analítico capaz de dar conta da participação de novos atores, de natureza não governamental, nas relações entre países em desenvolvimento − comumente denominada de cooperação Sul/Sul (CSS) − e suas implicações para a ampliação de direito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 31 publications
0
3
0
3
Order By: Relevance
“…The study showed that managers were not willing to tarnish their organizations' reputations, or their own professional reputations, by accepting funds from sponsors they suspect of not acting in a transparent manner. This outcome provides evidence of the growing pressure of society for transparency in CSO management processes (Mansur & Teodósio, 2016;P. Mendonça & Falcão, 2016).…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…The study showed that managers were not willing to tarnish their organizations' reputations, or their own professional reputations, by accepting funds from sponsors they suspect of not acting in a transparent manner. This outcome provides evidence of the growing pressure of society for transparency in CSO management processes (Mansur & Teodósio, 2016;P. Mendonça & Falcão, 2016).…”
Section: Discussionmentioning
confidence: 80%
“…Transparency in CSO practices plays an essential role in strengthening organizational legitimacy vis-à-vis potential donors, whether they are individuals, governments, or organizations (Mansur & Teodósio, 2016). But the transparency of CSOs is not enough, because the transparent actions of donors are also essential to this process.…”
Section: Transparencymentioning
confidence: 99%
See 1 more Smart Citation
“…Consonante a isso, a transparência das práticas das OSCs é central para o fortalecimento da legitimidade da organização perante potenciais doadores, sejam eles individuais, governamentais ou organizacionais (Mansur & Teodósio, 2016). Porém a transparência não cabe apenas às OSCs, a ação transparente por parte de doadores também é fundamental.…”
Section: Transparênciaunclassified
“…As OSCs são denominadas por diferentes termos, por exemplo: organizações voluntárias e organizações do terceiro setor. O termo OSC remete à compreensão de suas características gerenciais, políticas, de diversidade e de complexidade (Mansur & Teodósio, 2016). São organizações privadas, que não visam ao lucro, estabelecidas legalmente, com gestão própria e voluntária (Instituto de Pesquisa Econômica Aplicada [IPEA], 2020).…”
Section: Introductionunclassified